Rereading Dom Casmurro - aesthetic hybridity in Capitu - Eli Carter (Machado de Assis em Linha, 2014)
Although perhaps best known for Lavoura Arcaica (2001), an adaptation of Raduan Nassar's 1975 novel, the majority of Luiz Fernando Carvalho's professional activity has been in television, where, in addition to critically acclaimed telenovelas, he has directed adaptations of works by Eça de Queirós, Ariano Suassuna, Machado de Assis, Clarice Lispector, and Graciliano Ramos. Carvalho's audiovisual oeuvre has distinguished him as one of the most creative directors working in Brazil today and as the first full-fledged Brazilian television auteur. In 2008 Carvalho completed Capitu, an adaptation of Machado de Assis's masterpiece, Dom Casmurro (1899). This paper analyzes Carvalho's unique rereading of Machado's novel and the aesthetic hybridity that characterizes Capitu.